log 3 (3^(x+1) – 18) = 2

3^(log 3 (3^(x+1) – 18)) = 3^2

3^(x+1) – 18 = 9

3^(x+1) = 27

log 3 (3^(x+1) = log 3 (27)

x+1 = 3

x = 2

4 less steps.

]]>http://www.wolframalpha.com/input/?i=log3%283^%28x%2B1%29-18%29+%3D+2 ]]>

log 3 ( 3^(x+1) ) – 18 = log 3 (3^2)

3^(x+1) – 18 = 3^2

3^(x+1) – 18 – 3^2 = 0

3^(x+1) – 18 – 9 = 0

3^(x+1) – 27 = 0

3^(x+1) = 27

3^(x+1) = 3^3

x+1 = 3

x = 3-1

x = 2

(I just copied and pasted the other 2 guys’ response to look smart)

]]>x=(ln((100/3)+18)/ln3)-1.

]]>log 3 (3^(x+1) – 18) = 2

3^2 = 3^(x+1) – 18

9 = 3^(x+1) – 18

3^(x+1) = 9 + 18

3^(x+1) = 27

3^(x+1) = 3^3

x+1 = 3

x = 3 – 1

x = 2

]]>

log 3 ( 3^(x+1) ) – 18 = log 3 (3^2)

3^(x+1) – 18 = 3^2

3^(x+1) – 18 – 3^2 = 0

3^(x+1) – 18 – 9 = 0

3^(x+1) – 27 = 0

3^(x+1) = 27

3^(x+1) = 3^3

x+1 = 3

x = 3-1

x = 2

]]>